2004
DOI: 10.1002/hep.20490
|View full text |Cite
|
Sign up to set email alerts
|

Waning Immunity To Plasma–Derived Hepatitis B Vaccine and the Need for Boosters 15 Years After Neonatal Vaccination

Abstract: Neonatal immunization with hepatitis B (HB) vaccine is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
106
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(117 citation statements)
references
References 31 publications
10
106
0
1
Order By: Relevance
“…Otherwise, the higher immunogenicity, safety, efficacy of the recombinant DNA-derived hepatitis B vaccines than plasma-derived vaccine was reported by other researchers [Hayashi et al, 1988;Most et al, 1992;Soyletir et al, 1992]. Lu et al [2004] who found unacceptably high rates of undetectable anti-HBs among children who had received four doses of plasma-derived hepatitis B vaccine as the neonatal immunization 15 years previously. They results suggest that one or more booster immunizations are needed in seronegative subjects by at least 15 years following neonatal immunization with plasma-derived hepatitis B vaccine.…”
Section: Discussionmentioning
confidence: 88%
“…Otherwise, the higher immunogenicity, safety, efficacy of the recombinant DNA-derived hepatitis B vaccines than plasma-derived vaccine was reported by other researchers [Hayashi et al, 1988;Most et al, 1992;Soyletir et al, 1992]. Lu et al [2004] who found unacceptably high rates of undetectable anti-HBs among children who had received four doses of plasma-derived hepatitis B vaccine as the neonatal immunization 15 years previously. They results suggest that one or more booster immunizations are needed in seronegative subjects by at least 15 years following neonatal immunization with plasma-derived hepatitis B vaccine.…”
Section: Discussionmentioning
confidence: 88%
“…natural boosting by close contact to the carrier mother during infancy is believed to be instrumental. 7,11,21,22,[29][30][31][32]35,37,38 the association between longer gap time between the last and preceding dose of primary vaccination has been discussed in several other studies. 29,33,[44][45][46] this may be explained by a more mature immune system in older infants 31,33 and maturation of the immune memory during the longer interval between the last 2 doses as shown for polio, hepatitis B and hepatitis a vaccine in children and adults.…”
Section: Discussionmentioning
confidence: 99%
“…4,8,11,19,28,[31][32][33][34][35][36][37] Finally, both parameters may also be influenced by the prevalence of hepatitis B infection in the population and the HBsag carrier status of the mothers in the country. 6,7,11,21,22,[28][29][30][31][32][33]35,37,38 all these studies, however, are difficult to compare because results are influenced by a mixture of causes as well as by different follow-up periods.Based on a systematic review on studies providing information on the duration of anti-HBs ≥ 10 miu/ml persistence after hepatitis B vaccination started within the first 6 months of life and on the response to booster vaccination in individuals with antiHBs concentrations <10 miu/ml, we performed meta-analyses to identify relevant factors for duration of protection. a prognostic model to predict the proportion of vaccinated individuals likely to be protected is presented.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among a cohort of adolescents with maternal HBeAg positivity and who had developed protective levels of anti-HBs during infancy, the anti-HBc-positive rate was 33.3% at 15 years of age. 10 The anti-HBc-positive rates of the first decade in children of HBeAg-positive mothers were 9.5% and 14.3%, respectively, for whom with and without booster vaccination was at 5 years of age. 11 For their second decade of life, these rates were 22.2% and 28.6%, respectively.…”
Section: Replymentioning
confidence: 92%